2021
DOI: 10.1037/xan0000297
|View full text |Cite
|
Sign up to set email alerts
|

Two-item conditional same–different categorization in pigeons: Finding differences.

Abstract: Research on same-different categorization has shown that mastery of tasks of this kind can be strongly affected by the number of items in the training arrays-for both humans and nonhuman animals. Evidence for two-item same-different categorization in pigeons is decidedly mixed: although some investigations have succeeded, others have failed. To date, no research has documented successful conditional same-different categorization using just two items, nor has research explored how pigeons' responses in this par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
(96 reference statements)
0
3
0
Order By: Relevance
“…Ideally, S/D judgments can be accomplished with this minimal amount of information. This two-item capability has been found in pigeons using static visual images (Blaisdell & Cook, 2005;Diaz et al, 2021;Katz & Wright, 2006), but remains an area for more investigation. To examine this question, we took several avenues.…”
Section: Methodsmentioning
confidence: 75%
“…Ideally, S/D judgments can be accomplished with this minimal amount of information. This two-item capability has been found in pigeons using static visual images (Blaisdell & Cook, 2005;Diaz et al, 2021;Katz & Wright, 2006), but remains an area for more investigation. To examine this question, we took several avenues.…”
Section: Methodsmentioning
confidence: 75%
“…Those could be within or across other sensory modalities. S/D concept was extensively studied with several animals (Blaisdell and Cook, 2005;Cook and Wasserman, 2007;Truppa et al, 2011;Newport et al, 2015;Magnotti et al, 2017;Fuss et al, 2021) (see also reviews : (Chittka and Jensen, 2011;Katz et al, 2007;Wright et al, 2021)), various sensory modalities (Cook and Brooks, 2009) and many experimental protocols (Bodily et al, 2008;Diaz et al, 2021). Astonishingly and despite their tiny brains, invertebrates like ants (see review : (Czaczkes, 2022)), wasps (Weise et al, 2022) and bees (Brown and Sayde, 2013) were also shown to succeed in complex learning tasks (Finke et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…In relational match-to-sample tasks, participants are cued with a pair of stimuli that exhibit a given relationship (e.g., sameness, i.e., AA) and are then asked to match these with a target pair that exhibits an identical relationship (i.e., BB, not CD). These methods have frequently been used to test the perception and conceptualization of sameness and difference in non-human animals (for an overview, see Cook and Qadri 2021 ; Diaz et al 2021 ; Lazareva and Wasserman 2017 ; Scagel and Mercado 2023 ; Wasserman et al 2017 ). Based on the results of these studies, it is acknowledged that many species of animals are capable of learning concepts that presuppose detecting and classifying sameness and difference; examples of these animals include bottlenose dolphins (e.g., Mercado et al 2000 ), sea lions (e.g., Kastak and Schusterman 1994 ), parrots (e.g., Pepperberg 1987 ), primates (e.g., Wright and Katz 2006 ), pigeons (e.g., Cook and Brooks 2009 ), dogs ( Scagel and Mercado 2023 ), bumblebees ( Brown and Sayde 2013 ) and honey bees ( Giurfa 2021 ).…”
Section: Introductionmentioning
confidence: 99%